Edukasi Stunting dan Pencegahannya pada Ibu Hamil di Puskesmas Putri Ayu Kota Jambi - Maimaznah, Maimaznah; Indrawati, Iin; Hesty, Hesty (Prosiding Seminar Kesehatan Nasional, 2024)
Stunting is a condition of failure to thrive and chronic nutritional problems caused by inadequate nutritional intake due to the provision of food that does not meet the needs of the long term. The causes of stunting are factors of poor nutrition experienced by pregnant women and children under five, limited health services including services for ante-natal care, post-natal care, lack of access to nutritious food and lack of maternal knowledge regarding health and nutrition before and during pregnancy, as well as after the mother gives birth. In 2021, out of 27,615 toddlers in Jambi City, 179 toddlers are stunted. To date, of 31,373 toddlers, there are 803 toddlers experiencing stunting or 2.56%. For Jambi City, the prevalence of stunting under five in 2021 is 17.4%. Based on the preliminary survey that has been conducted, many mothers do not understand the knowledge, attitudes, and practices in preventing stunting. Based on an initial survey conducted at the Putri Ayu Health Center on 10 pregnant women, there were 7 pregnant women who still did not know how to prevent stunting in children. The health problems above are carried out as a solution to the problem and followed up in order to prevent stunting in children. Therefore the author does community service in this case providing education regarding the prevention of stunting in children by educating pregnant women at the Putri Ayu Health Center, Jambi City. The purpose of this activity is to provide education about stunting and its prevention so as to increase knowledge in preventing stunting with the target of pregnant women at PKM Putri Ayu. This activity was carried out for 6 months, starting from March - August 2023. The method used was by giving education 1x by giving a pre and post test to assess changes in knowledge before and after being given education. The resulting outputs are in the form of increased knowledge of pregnant women regarding stunting prevention and scientific publications in accredited journals